Effect of Adding Feed Fermentation of Sago Pulp on The Palatability of The Peranakan Etawa - I. Irwansyah; I. Junaedi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2019)
The purpose of this research is to know the effect of adding feed fermentation of sago pulp to the palatability level of the breeds of Etawa. In this study used 9 goat cattle PE age 6 months with an average initial body weight of 17 kg. Materials used include sago pulp, probion, bran, urea and molasses. Complete feed prepared from the material is sago pulp 75%, bran 20%, urea 0.25%, molasses 3% and minerals 1.25%. While the probion is added as much as 0.5% of the total feed ingredients. All feed ingredients are mixed and then fermented anaerobic for 21 days. Feeding is done according to the treatment of (100% natural grass + 0% fermented feed, 70% natural grass + 30% fermentation feed, 50% natural grass + 50% fermented feed). The observed variable is palatability. The research draft uses complete random design. Feeding with the addition of fermentation of sago pulp 30%, the consumable level 859.56 grams/day higher (P0.01) from the fermentation of sago pulp 50% (773.38 gram/tail/day) and without the feeding of sago pulp (697.62 gram/tail/day